A Transcriptional Regulatory System of the S. cerevisiae OLE1 Gene Responds to Fatty Acid Species and Intracellular Amount, and not Simply Membrane Status. (25th January 2020) - Willey, Marshall; Ochs, Matt; Busse, Clara; McDonough, Virginia
Abstract : We examined the effects of unsaturated fatty acid (UFA) species and their concentration on the expression of OLE1, which encodes the stearoyl CoA desaturase, in Saccharomyces cerevisiae . We controlled the amount of UFA taken up by the cell by varying the concentration of tergitol in the medium. When cultured with 1 mM fatty acid in 0.1% tergitol, cells took up much more fatty acid than when cultured with the same concentration of fatty acid at 1% tergitol, although the amount incorporated was dependent on UFA species. For each fatty acid tested, we found that the higher uptake (0.1% tergitol condition) had a stronger impact on OLE1 regulation. A principal product of the desaturase 16:1∆9, and the nonnative UFA 18:2∆9, 12, most strongly repressed the reporter construct OLE1-lacZ transcription, while the other major product of the desaturase, 18:1∆9, and the nonnative UFA 17:1∆10 caused a more diminished response. Based on these results, our initial hypothesis was that OLE1 was regulated in response to membrane fluidity; however, subsequent work does not support that idea; we have found that conditions that affect membrane fluidity such as growth temperature and growth with saturated or trans fatty acid supplementation, do not regulate OLE1 in the direction predicted by fluidity changes. We conclude that at least one signal that regulates OLE1 transcriptional expression is most likely based on the fatty acids themselves.